2020
DOI: 10.1038/s41598-020-68995-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 attenuates OxPCs-mediated lipid metabolic responses in ischemia reperfusion injury

Abstract: Oxidized phospholipids (OxPLs) promote inflammation as well as low density lipoprotein (LDL) uptake in a variety of physiological and pathological states. Given the anti-inflammatory role of the cytokine IL-10, we investigated its modulatory effect on the production of oxidized phosphatidylcholines (OxPCs) as well as lipid metabolic responses in global myocardial ischemia/reperfusion (I/R) injury. Increased OxPCs levels, by 1-Palmitoyl-2-(5-oxovaleryl)-sn-glycero-3-phosphocholine (POVPC), promoted oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
(91 reference statements)
2
9
0
Order By: Relevance
“…The anti-inflammatory role of IL-10 was suggested to contribute to reduced levels of IL-6 and TNF-α. Furthermore, in ischemia-reperfusion injury animal models, IL-10 mitigated inflammation and cardiomyocyte death by attenuating oxidized phospholipids-mediated lipid metabolic responses [ 67 ]; these findings in corroboration with our study support the potential of IL-10 therapy for the treatment of inflammatory diseases and conditions including CVD.…”
Section: Discussionsupporting
confidence: 88%
“…The anti-inflammatory role of IL-10 was suggested to contribute to reduced levels of IL-6 and TNF-α. Furthermore, in ischemia-reperfusion injury animal models, IL-10 mitigated inflammation and cardiomyocyte death by attenuating oxidized phospholipids-mediated lipid metabolic responses [ 67 ]; these findings in corroboration with our study support the potential of IL-10 therapy for the treatment of inflammatory diseases and conditions including CVD.…”
Section: Discussionsupporting
confidence: 88%
“…We have reported that TLR2 dominates over TLR4 regulation through NF-kB mediated pathway and activation of IRAK2/M [ 23 , 24 ]. Later, we have shown that increased OxPCs may have worsen the I/R injury via TLR2 upregulation controlled by LOX-1 [ 44 ]. We now assume that iNOS is a major downstream mediator of inflammation in cardiomyocytes and causes DIC.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that changes in CL, PC, phosphatidylinositol monomannoside, sphingomyelin, sulfatide, and ambiguous or unidentified lipids occur mainly after 48 h of I/R (I/R-48) and normalized or suppressed at I/R-72. ROS also increase the levels of oxidative phosphatidylcholines (OxPCs) in the I/R injury in the heart [ 46 ]. OxPCs may trigger apoptosis through phosphorylation of p38 mitogen-activated protein kinase (p38MAPK).…”
Section: Lipidomicsmentioning
confidence: 99%
“…There is ample evidence of adverse accumulation of FAs in renal I/R injury, which ultimately may give rise to lipotoxicity [ 27 , 46 ]. The term “lipotoxicity” refers to the condition with an unwanted accumulation of lipids in non-adipose tissues that are incapable of metabolizing them.…”
Section: Lipid Metabolism In I/r Injurymentioning
confidence: 99%